Bread without wheat - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
New ways of making bread from cassava and sorghum could reduce the dependence of the Third World on imported wheat for white bread, according to FAO, who have been researching this for two years. Traditional staples have been rejected in developing...